Implementasi Pendekatan Arsitektur Ekologis Pada Ekowisata Dusun Bambu Bandung - Aprillianto, Cahya; Soaduon Panjaitan, Tigor Wilfirtz; Rolalisasi, Andarita (Jurnal Etnik: Ekonomi-Teknik, 2024)
One of the development sectors of the Indonesian nation is tourism. In the government's efforts to improve the welfare and prosperity of the people, tourism is expected to make a major contribution to increasing the country's foreign exchange (Tri et al., 2014). Tourism has several approach concepts that can be applied, one of which is ecology or ecotourism. Ecotourism is sustainable tourism that focuses on nature management to increase understanding and appreciation of environmental and cultural conservation (Nurul et al., 2021). According to the International Ecotourism Society (TIES) (1991) ecotourism is tourist travel to natural areas to conserve or save the environment and provide a livelihood to local residents. According to this definition, ecotourism is a natural tourism trip with special interests carried out in accordance with environmental conservation standards (Idham, 2020). Ecological tourism or ecotourism is now widely spread in Indonesia, one of which is Dusun Bambu Bandung. Dusun Bambu offers one stop leisure on 15 hectares of land located at the foot of Mount Burangrang. The main concept of Dusun Bambu is ecotourism and conservation with mission 7E, which means Education, Economy, Ethnology, Ethics, Aesthetics and Entertainment. Dusun Bambu received the ASEAN Sustainable Tourism Award (ASTA) and Indonesia Sustainable Tourism Award (ISTA) which is proof of the success of Dusun Bambu as a sustainable tourist destination. By applying ecological principles to Dusun Bambu, it can reduce the negative impacts produced by conventional tourism in general.